Use of indocyanine green and the HyperEye system for detecting sentinel lymph nodes in breast cancer within a population of European patients: a pilot study - Coufal, Oldřich; Fait, Vuk (World journal of surgical oncology, 2016)
BACKGROUND: Certain studies suggest that using indocyanine green (ICG) could be comparable with using radioisotopes (RI) in detecting sentinel lymph nodes (SLNs) in breast cancer. A number of these studies were performed in Asia. The objective of our pilot study was to evaluate within a European population of breast cancer patients the detection rate of SLNs using ICG and the HyperEye system and the concordance in SLNs detected using this method and the standard method involving RI and a gamma probe. METHODS: Ten female patients with early-stage breast cancer (Czech Republic) indicated for partial mastectomy and SLN biopsy were subjected to standard application of RI. Before surgery, ICG was administered periareolarly in the amount of 1 ml of 0.5% solution. Sentinel lymph nodes were first detected perioperatively exclusively using ICG fluorescence and the HyperEye device (Mizuho, Japan). Only after removal of all SLNs found in this way was the standard hand-held gamma probe used to detect RI, and any potential additional SLNs not found with ICG were then extirpated. RESULTS: In all 10 cases, at least one SLN was successfully detected using ICG. Nevertheless, in five patients, 1-4 additional SLNs were found using the gamma probe. Complete concordance in detecting SLNs therefore occurred in only one half of the cases. Metastases in SLNs were found in a total of two cases. Had we used only ICG for detection, one of these two cases would have been incorrectly evaluated as N0 (ICG false negativity). CONCLUSIONS: The study did not confirm the hypothesis that the use of ICG with the HyperEye system can currently be considered a method fully comparable with using RI and a gamma probe in a population of European patients. Although the detection rate is high, a significantly lower number of SLNs were detected using ICG than using RI (p = 0.03). Thus, there would be a higher probability for false negatives to occur in using SLN biopsy. This is caused mainly by the limited permeability of tissues to fluorescent radiation and the difficulty therefore of detecting nodes located deeper beneath the body's surface.
Keywords: fluorescenční barviva; Radioactive Tracers; sentinelová uzlina; technecium 99mTc-agregovaný albumin; Breast Neoplasms; Mastectomy; Indocyanine Green; Fluorescence; Sentinel Lymph Node Biopsy; Fluorescent Dyes; indokyanová zeleň; Česká republika; lymfatické metastázy; radioaktivní indikátory; HyperEye; fluorescence; Czech Republic; Breast cancer; injekce intradermální; Lymphatic Metastasis; Neoplasm Staging; Injections, Intradermal; ultrasonografie; Technetium Tc 99m Aggregated Albumin; ženské pohlaví; Sentinel lymph node biopsy; Humans; Indocyanine green; pilotní projekty; Sentinel Lymph Node; Pilot Projects; nádory prsu; Ultrasonography; staging nádorů; biopsie sentinelové lymfatické uzliny; Female; mastektomie; lidé